Investigation of Multidentate Ligand complexes with Some Late Transition Metal Ions - Upadhya, Poonam; Nayan, Ram (Asian Journal of Chemistry, 2010)
Formation of the species MHA (M = Ni2+, Cu2+, Pd2+, Cd2+), MA, MA(OH), M2A (M = Cu2+ or Pd2+), Pd2A(OH), MHB (M = Ni2+, Zn2+, Pd2+, Ag+ or Cd2+) and MB (M = Ni2+, Zn2+, Pd2+ or Ag+ [where A = pentaanion of 1-hydroxy-8-(2-hydroxy-naphthylazo )-2-(sulphonaphthylazo)- 3,6-disulphonic acid and B = tetraanion of 2-hydroxy-1-(2-hydroxy- 4-sulpho-1-naphthylazo )-3-naphthoic acid] has been inferred in aqueous solution in pH-metric experimental measurements of the corresponding metal-ligand mixtures. Equilibrium constants related to the complex species present have been evaluated at 25°C (μ = 0.10 M KNO3) and involvement of the ligand donor groups in coordination, under different ratios of the reactants and pH variations of the reaction mixtures, have been discussed.